Crossbreeding of exotic and indigenous cattle in Nigeria. Haematological correlates - Amakiri, S.F.; Ngere, L.O.; Olusanya, S.K.; Ikede, B.O. (Springer, 1979)
The blood values of the German Brown, N'Dama and their three-quarter, half and quarter hybrids were studied to ascertain the effects of crossbreeding on haematological parameters. The red blood cell (RBC) and white blood cell (WBC) counts and packed cell volume percentage (PCV) were significantly higher (p